Potensi Spent Mushroom Substrate (SMS) dari Limbah Tandan Kosong Sawit (TKS) Sebagai Green Biosorben - Yenie, Elvi; Darmayanti, Lita; Martina, Atria; Priscilia P Girsang, Yemima; Desce P Simarmata, Stella (Universitas Andalas, 2025)
Spent mushroom substrate (SMS) is an organic compost medium produced from the mushroom cultivation process. The chemical composition of SMS includes 22.86% cellulose, 19.71% hemicellulose, and 10.24% lignin. The aim of this study is to determine the optimal biosorbent mass for lead (Pb) heavy metal biosorption and to analyze the characteristics of the best biosorbent using tests such as SEM, BET, XRD, FTIR, and lignocellulosic tests. The constant variables used are a contact time of 30 minutes, a stirring speed of 150 rpm, and a biosorbent size of 100 mesh. The variable to be tested is the biosorbent mass (0.5, 1, 1.5) grams. The results showed that the highest removal occurred with a biosorbent mass of 0.5 grams, with a biosorption capacity of 1.160 mg/g and an efficiency of 65%. SMS has rough, cracked, porous, and fragmented pores, with a surface area of 1.4666 m²/g, a pore size of 43.1569 Å, and a crystallinity degree of 1.89% from 5.30%. The lignin content is 13.93%, hemicellulose 9.25%, and cellulose 16.15%, while FTIR testing indicates the presence of hydroxyl, amino, carbonyl, and phosphate groups. Keyword: Heavy Metal Pb, biosorption, characterization, Spent Mushroom Substrate